Penerapan Metode MOORA Dalam Pemilihan Bimbingan Belajar Terbaik - Sriwahyuni Hutagalung; Dinda Saputri Gea; Dwina Pri Indini; Mesran (Journal of Informatics Management and Information Technology, 2023)
Tutoring is one of the most effective alternatives that can be used by parents who want to provide additional courses or tutoring to their children, bearing in mind that learning at school is less effective if it is only obtained at school, especially for students who wish to continue their tertiary education so students need additional tutoring. to deepen the material so that later you can pass the desired tertiary institution. Tutoring is one of the activities that involves teaching students so that they achieve maximum academic achievement or learning outcomes at the institution or place where they study. from the research on the Application of Multi-Objective Optimization on the basis of Ratio Analysis (MOORA) in the Selection of the Best Tutoring, namely that it can make it easier for writers to solve complex problems by using a decision support system and the results of calculations applied by the writer which cannot be changed by anyone. because the results are absolute and real without any fraud in the calculation process using ROC (Rank Order Centroid) weighting which is useful for calculating the value of tutoring criteria effectively with the Multi-Objective Optimization on the basis of Ratio Analysis (MOORA) method. Tutoring is a non-formal institute that has more effective and reliable teaching quality for the last 5 years. by implementing a decision support system using the MOORA method and ROC weighting can help provide accurate results in selecting the best tutoring. There are three criteria, namely Price, Installment Amount, Discount Type. The results of selecting the best tutoring using the MOORA method are A4 with a score of 11.7171 as rank 1 on behalf of the ASC institution.